2012
DOI: 10.1158/1078-0432.ccr-12-1595
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL and Noxa Are Selectively Upregulated in Prostate Cancer Cells Downstream of the RIG-I/MAVS Signaling Pathway by Nonreplicating Sendai Virus Particles

Abstract: Purpose: The treatment of cancer with oncolytic viruses primarily depends on the selective viral replication in cancer cells. However, a replication-incompetent hemagglutinating virus of Japan (HVJ; Sendai virus) envelope (HVJ-E) suppresses the growth of human cancer cells as effectively as replicationcompetent live HVJ without producing toxic effects in nonmalignant cells. Here, we analyze the molecular mechanism of the oncolytic activity of HVJ-E.Experimental Design: The molecules responsible for HVJ-E-induc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 45 publications
4
92
0
Order By: Relevance
“…So far, only dsRNA cytosolic receptors have been implicated in the apoptotic effect induced by transfected poly(I:C) or viral dsRNA in prostate, gastric, breast, and melanoma cancers (20,(43)(44)(45). The most specific cytosolic receptor for poly(I:C) was demonstrated to be MDA5 (46), which mainly mediates antitumor effects (45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, only dsRNA cytosolic receptors have been implicated in the apoptotic effect induced by transfected poly(I:C) or viral dsRNA in prostate, gastric, breast, and melanoma cancers (20,(43)(44)(45). The most specific cytosolic receptor for poly(I:C) was demonstrated to be MDA5 (46), which mainly mediates antitumor effects (45).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, to confirm the canonical role of IRF3 in IFN type I induction, we transfected PC3 cells with a plasmid containing luciferase under the IFN-␤ promoter and assayed the luciferase activity after poly(I:C) alone and in combination with the IRF3 inhibitor BX795 for 3 h. DU145 cells were not tested because they have been described as not being able to produce IFN type I after poly(I:C) treatment (20). The pretreatment with BX795 abrogates the induction of IFN-␤ transcription, demonstrating the key role of IRF3 in the activation of the IFN-␤ promoter …”
Section: (Error Bars)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we reported that HVJ-E stimulates an antitumor immune response by activating cytotoxic T lymphocytes and natural killer cells and suppressing regulatory T cells (25,26). Among these direct and indirect HVJ-E antitumor activities, we recently discovered that HVJ-E induces apoptosis via activation of the retinoic acid-inducible gene-I (RIG-I)/mitochondrial antiviral-signaling protein pathway followed by activation of interferon regulatory transcription factor (IRF)3 or IRF7 in prostate cancer cells (27). HVJ is a mouse parainfluenza virus that belongs to the paramixoviridae genus.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, T/N ratio of cell death in PDT was higher than that of PE uptake. It is known that selective apoptosis in PC-3 cells but not in PNT2 cells is induced via recognition of fragmented HVJ-E's RNA genome by intracellular retinoic acid-inducible gene-I whose signaling pathway selectively activates apoptosis-inducing ligands in PC-3 cells [26]. In this study, survival rates of PC-3 cells were lower than those of , respectively.…”
Section: Discussionmentioning
confidence: 66%